PENGARUH RELATED PARTY TRANSACTION TERHADAP TAX AVOIDANCE DENGAN VARIABEL MODERASI PENGUNGKAPAN TATA KELOLA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - Chindy Helfin, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to obtain empirical evidence on the effect of related party transaction to tax avoidance with corporate governance disclosure as a moderating variable that listed in Indonesia Stok Exchange, with a total of 109 samples. This study uses secondary data which were tested using software SmartPLS 3,0. The result of this study suggests that related party transaction significantly influence tax avoidance. However, corporate governance disclosure doesn’t moderate the effect of related party transaction on tax avoidance.